FINANCIAL PERFORMANCE: SUSTAINABILITY, SIZE, SHARIAH, AND SECTOR EFFECTS IN MUSLIM-MINORITY STOCK EXCHANGES - Kartikasari, Dwi (Journal of Islamic Monetary Economics and Finance, 2023)
Sustainability and halal stocks have become increasingly popular in the digital and globalized world after the COVID-19 pandemic, even in Muslim-minority developed countries. This study examines whether there exist sustainability, size, Shariah compliance, sector, and stock exchange effects in financial performance. We collect the cross-section data for 2022–2023 covering 270 public-listed companies. These include earning-per-share (EPS) representing performance, market capitalization representing firm size, and business sectors from Compustat, halal status and level from Musaffa, and Environmental, Social, and Governance (ESG) rating and risk representing sustainability from Sustainalytics. Using the partial least square structural equation model (PLS-SEM), we discover the significance of sustainability and size but the debatably significant moderating effect of Shariah, sector, and stock exchange on performance. We explain these findings by the Stakeholder Theory and Resource-Based View. These results should prove beneficial to managers in backing their green and Shariah compliance strategies for financial performance.